Effect of nano calcium carbonate and attapulgite on isothermal crystallization time of polypropylene under static and dynamic conditions. Issue 3 (February 2019) - Yuan, Song; Li, Yi; Zhang, Qiong; Wen, Jun
Abstract: The isothermal crystallization time of polypropylene/nano calcium (PP/CaCO3 ) and polypropylene/attapulgite (PP/ATP) under static and dynamic conditions were investigated by using differential scanning calorimeter and Rheological experiments. Relatively, in static conditions, the calcium carbonate was easier to accelerate the crystallization process due to its shape. In the shear field the attapulgite is more advantageous to shorten crystallization time indicating that the attapulgite dispersed in the PP matrices confined the PP chains and hindered the movement of the PP chains.